Interactive effects of co-occurring anthropogenic stressors on the seagrass, Zostera noltei. (February 2020) - Vieira, Raquel; Martin, Airam; Engelen, Aschwin H.; Thomsen, Mads S.; Arenas, Francisco
Highlights: We study the impacts of seaweed, nutrient and sediment loading on eelgrass beds. Sediment loading and invasive seaweeds had the most negative impacts. Non-additive interactions were detected, specially related to nutrient enrichment. Indirect effects of the stressors are suggested, linked with changes in the fauna. Abstract: Coastal ecosystems are subjected to multiple co-occurring anthropogenic stressors which potentially interact to produce complex impacts on the structure and functioning of biological communities. Seagrass meadows are among the most rapidly declining coastal habitats on Earth. In particular, high nutrient loadings, enhanced sedimentation and competition from blooming seaweeds, like the invasive red alga Gracilaria vermiculophylla, are claimed to be associated with this decline. In this study, we tested for individual and potential interactive impacts on the intertidal seagrass Zostera noltei of these three stressors using a factorial field experiment. We measured seagrass shoots density and biomass (both above and below ground seagrass biomass) as proxies of seagrass physical condition. We also examined changes in fauna assemblages. The study suggested that sediment loading had the most detrimental impacts on health of the seagrass meadows. The effect of seaweed addition was negative and denso-dependent. Deleterious effects of nutrient enrichment were less evident. Non-additive interactions were also noticeable for some of the structural traits measured. Particularly, nutrient enrichment changed the effect of the other stressors for some of the responses measured. The effect of the treatments was also perceptible in the associated fauna assemblages. The ubiquitous grazer Peringia ulvae was more abundant in treatments with sediment loading, but those sediment effects in the density of the small grazer were modulated by nutrient and seaweed addition levels. Finally, we suggest that more studies should test for synergistic effects of co-occurring stressors to better understand the direction and intensity of changes triggered by human activities in natural ecosystems.